(untitled) (Journal of Management and Social Sciences, 2021)
Female underrepresentation in Science, Technology Engineering and Mathematics (STEM) related disciplines is a global educational concern. Though females outnumber males at undergraduate level in higher educational institutions, the number tends to reduce at the postgraduate level and relatively few are represented in academia as they navigate the gendered terrain of STEM pursuing their academic career. Thus, few hold leadership positions. The thrust of this paper is to investigate how female lecturers navigate the gendered STEM path, interrogate the persistent leaky pipeline women encounter as they climb the ladder in their career. It further explores ways the paths conform to and diverge from traditional institutional norms. The paper adopts qualitative method of data collection using in-depth interview with respondents consisting of both male and female lecturers purposively selected from STEM related departments in four purposively selected Universities; University of Ibadan, University of Maiduguri, Federal University, Otuoke and Usmanu Dan Fodio University in the different ranks of their careers. Hinged on intersectionality theory, findings showed that there exists a sort of micro-politics which men play. Women who can negotiate properly will progress successfully albeit at a slower pace than the men, thus not all women experience the leaky pipeline the same way. This research helps provide a clearer way for women to navigate their path in STEM related fields and the advantage of the participation of women in this fields. Keywords Women, STEM, leaky pipeline, gendered path, Higher Education Institutions